2018
DOI: 10.3389/fpsyg.2018.00568
|View full text |Cite
|
Sign up to set email alerts
|

tDCS Stimulation of the dlPFC Selectively Moderates the Detrimental Impact of Emotion on Analytical Reasoning

Abstract: There is evidence of a detrimental effect of emotion on reasoning. Recent studies suggest that this relationship is mediated by working memory, a function closely associated with the dorsolateral prefrontal cortex (dlPFC). Relying on transcranial direct current stimulation (tDCS), the present research explores the possibility that anodal stimulation of the dlPFC has the potential to prevent the effect of emotion on analytical reasoning. Thirty-four participants took part in a lab experiment and were tested twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, the stimulation effect lasted for two months. The reduced perceived pain intensity seems to be due to synaptic plasticity and neuronal survival in the primary motor cortex and DLPFC region, because DLPFC may be activated during painful states and, as a result, modulate the structures involved in emotional pain perception, such as the anterior cingulate cortex, insula, and amygdala (Dubreuil-Vall et al, 2019;Li et al, 2022;Trémolière et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the stimulation effect lasted for two months. The reduced perceived pain intensity seems to be due to synaptic plasticity and neuronal survival in the primary motor cortex and DLPFC region, because DLPFC may be activated during painful states and, as a result, modulate the structures involved in emotional pain perception, such as the anterior cingulate cortex, insula, and amygdala (Dubreuil-Vall et al, 2019;Li et al, 2022;Trémolière et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This montage was used because of the likely effect of stimulation at this site on the left dorsolateral prefrontal cortex. This area of the brain was chosen for stimulation as it is known to be involved in complex executive functions such as control of cognitive processes and attention ( Leh et al, 2010 ; Brosnan and Wiegand, 2017 ), and previous research has shown that its stimulation may affect relevant executive cognitive functions ( Elmer et al, 2009 ; Javadi and Walsh, 2012 ; Trémolière et al, 2018 ; Angius et al, 2019 ). We also completed a computer simulation analysis of the likely current density that would result from the chosen montage ( Figure 1 ) using commercially available software (HD Explore; Soterix Medical, Woodbridge NJ, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Relative to neutral feedback, negative feedback elicited greater functional connectivity between the dorsolateral prefrontal cortex (dlPFC) and visual cortex in the foreign language, but not in the native language. Given the role of the dlPFC in cognitive control processes [81,82], as well as analytic reasoning [83], the authors propose that using a foreign language may engage increased control processes to divert attention away from negative stimuli.…”
Section: Estimating Risks: What Is the Likelihood That Things Will Go Wrong?mentioning
confidence: 99%